The Rice High-Affinity K+ Transporter OsHKT2;4 Mediates Mg2+ Homeostasis under High-Mg2+ Conditions in Transgenic Arabidopsis - Zhang, Chi; Li, Hejuan; Wang, Jiayuan; Zhang, Bin; Wang, Wei; Lin, Hongxuan; Luan, Sheng; Gao, Jiping; Lan, Wenzhi (Frontiers in Plant Science, 2017)
ABSTRACT Rice (Oryza sativa; background Nipponbare) contains nine HKT (high-affinity K+ transport)-like genes encoding membrane proteins belonging to the superfamily of Ktr/TRK/HKT. OsHKTs have been proposed to include four selectivity filter-pore-forming domains homologous to the bacterial K+ channel KcsA, and are separated into OsHKT1s with Na+-selective activity and OsHKT2s with Na+-K+ symport activity. As a member of the OsHKT2 subfamily, OsHKT2;4 renders Mg2+ and Ca2+ permeability for yeast cells and Xenopus laevis oocytes, besides K+ and Na+. However, physiological functions related to Mg2+ in planta have not yet been identified. Here we report that OsHKT2;4 from rice (Oryza sativa; background Nipponbare) functions as a low-affinity Mg2+ transporter to mediate Mg2+ homeostasis in plants under high Mg2+ environments. Using the functional complementation assay in Mg2+-uptake deficient Salmonella typhimurium strains MM281 and electrophysiological analysis in Xenopus laevis oocytes, we found that OsHKT2;4 could rescue the growth of MM281 in Mg2+-deficient conditions and induced the Mg2+ currents in oocytes at millimolar range of Mg2+. Additionally, overexpression of OsHKT2;4 to Arabidopsis mutant lines with a knockout of AtMGT6, a gene encoding the transporter protein necessary for Mg2+ adaptation in Arabidopsis, caused the Mg2+ toxicity to the leaves under the high Mg2+ stress, but not under low-Mg2+ environments. Moreover, this Mg2+ toxicity symptom resulted from the excessive Mg2+ translocation from roots to shoots, and was relieved by the increase in supplemental Ca2+. Together, our results demonstrated that OsHKT2;4 is a low-affinity Mg2+ transporter responsible for Mg2+ transport to aerials in plants under high Mg2+ conditions.